The impact of HIV on clinical-microbiologic features and mortality among patients with invasive nontyphoidal Salmonella infection in South Africa - Mtandu, Rugola (My University, 2009)
Introduction: Nontyphoidal Salmonella (NTS) has been associated with HIV from the outset of the HIV pandemic. The few NTS studies done in Africa and America have not documented the impact of HIV on clinical-microbiologic features and mortality in patients with NTS infection. This study determined the association between HIV serostatus and mortality proportion, clinical presentation, length of hospital stay, frequency of invasive NTS infection recurrence, NTS serotypes and estimated the population attributable fraction of mortality due to HIV among patients with invasive NTS infection in South Africa. Methods: Secondary data from enteric diseases national surveillance in South Africa from 2003 to 2006 were analysed as a cross sectional study. A total of 1 398 subjects with known HIV serostatus were obtained after data cleaning. Data analysis was done in Stata using chi squared test for categorical variables and Wilcoxon rank sum test / Kruskal- Wallis test for continuous variables. Logistic regression models were used to quantify the associations, and adjust for confounders and effect modification. Population attributable fraction was calculated to quantify the impact of HIV on mortality. Results: Majority (82.26%) of patients were HIV positive. The frequency pattern of HIV positive serostatus in different age groups coincided with that of invasive NTS. The overall mortality was 32.00%. HIV positive patients had a higher proportion (35.79 %) of mortality than HIV negative patients (15.55 %) (P<0.001). Fifty five percent of deaths in this study population were attributed to HIV infection. In multivariate models, HIV positive patients were more likely than HIV negative patients to die (OR = 2.50, 95% CI 1.69- 3.70), to develop lower respiratory tract infection (LRTI) (OR = 1.89, 95% CI,1.34- 2.65), to have recurrence of invasive NTS (OR = 3.90, 95% CI 1.41-10.77), to stay less than 16 days in hospitals (OR = 1.61, 95% CI, 1.08-2.40) and to be infected with Salmonella serotype Typhimurium infection (OR = 2.59, 95% CI 1.91-3.51). There were no significant differences in temperature, cardiac arrest, meningitis and site of specimen isolation (p>0.05). Discussion: The major limitation to this study was poor data quality of the surveillance system, including missing HIV serostatus hence the findings cannot be generalized to patients with unknown HIV status. Conclusion: HIV infection is common among patients with invasive NTS and is associated with excess mortality, LRTI, fewer than 16 days of hospital stay, recurrent invasive NTS infection and Salmonella Typhimurium. It is important for clinicians to rule out HIV infection in patients with invasive NTS especially those presenting with LRTI and Salmonella Typhimurium infection in addition to recurrent NTS infection, which is a wellknown feature associated with HIV. Recommendation: Since these patients received antimicrobials and had considerable mortality, the first line treatment of invasive NTS should be reviewed especially to HIV positive patients by investigating resistance patterns and conducting a clinical trial of newer and effective antimicrobials.
Keywords: nontyphoidal Salmonella; HIV; patients; impact; South Africa